Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Pada MANDIRI COLLECTION - Endah Kristiani; Lintang Pamugar Mukti Aji (JURNAL ILMIAH EDUNOMIKA, 2023)
This study discusses the Analysis of Liquidity Ratios, Solvency, Activity and Profitability. In assessing the Mandiri Collection's Financial Performance, the aim of this study was to determine conditions and performance based on financial ratios. The research data used uses primary data and secondary data. This type of research is descriptive quantitative which aims to find factual information. The objects used are financial reports in the form of balance sheets and Mandiri Collection profit/loss reports. In the 2018 and 2019 periods. In the data analysis method, the quantitative analysis method was used. The results of this study can be seen based on liquidity and solvency ratios. In the position of Debt to Asset ratio in 2018 to 2019 in very good condition. When viewed from the ratio of the effectiveness level of Mandiri Collection based on Inventory turn Over from 2018 to 2019, the operation can be categorized as effective. The Profitability ratio can be seen in the Return on Investment and Return on Equity and analysis of the profitability ratios that have been carried out from 2018 to 2019 has increased.